Spinal Surgery in Patients Aged 80 Years and Older: Risk Stratification Using the Modified Frailty Index. Issue 4 (May 2021) - Kweh, Barry; Lee, Hui; Tan, Terence; O'Donohoe, Tom; Mathew, Joseph; Fitzgerald, Mark; Gantner, Dashiell; Kambourakis, Tony; Tew, Kim; Hunn, Martin; Rosenfeld, Jeffrey; Tee, Jin
Study Design: This was an ambispective clinical quality registry study. Objective: To evaluate utility of 11-variable modified Frailty Index (mFI) in predicting postoperative outcomes among patients ≥80 years undergoing spinal surgery. Methods: Consecutive patients ≥80 years who underwent spinal surgery between January 1, 2013, and June 30, 2018, were included. Primary outcome measure was rate of major complication. Secondary outcome measures were (1) overall complication rate, (2) surgical site infection, and (3) 6-month mortality. Results: A total of 121 operations were performed. Demographic metrics were (1) age (mean ± SD) = 83.1 ± 2.8 years and (2) mFI (mean ± SD) = 2.1 ± 1.4 variables. As mFI increased from 0 to ≥4 variables, risk of major complication increased from 18.2% to 40.0% ( P = .014); overall complication increased from 45.5% to 70.0% ( P = .032); surgical site infection increased from 0.0% to 25.0% ( P = .007). There were no significant changes in risk of 6-month mortality across mFIs ( P = .115). Multivariate analysis showed that a higher mFI score of ≥3 variables was associated with a significantly higher risk of (1) major complication ( P = .025); (2) overall complication ( P = .015); (3) surgical site infection ( P = .007); and (4) mortality ( P = .044). Conclusions: mFI scores of ≥3/11 variables were associated with a higher risk of postoperative morbidity in patients aged ≥80 years undergoing spinal surgery. The mFI-associated risk stratification provides a valuable adjunct in surgical decision making for this rapidly growing subpopulation of patients.